An Operando calorimeter for high temperature electrochemical cells. (6th April 2021) - Young, David; Jackson, Ariel; Fork, David; Sadat, Seid; Rettenwander, Daniel; Benck, Jesse D; Chiang, Yet-Ming
Abstract: Operando calorimetry has previously been utilized to study electrochemical reactions and degradation in electrochemical cells such as batteries. Calorimetric data can provide important information on the lifetime and thermal properties of electrochemical cells in practical engineering applications such as thermal management. High temperature electrochemical cells such as solid oxide fuel cells or electrolyzers can also benefit from operando calorimetry, but to the authors' knowledge such capabilities have not been commercially developed. Herein, an operando calorimeter is reported that is capable of simultaneous calorimetry and electrochemistry at temperatures up to 1000 °C and in both oxidizing and reducing atmospheres. The calorimeter is constructed by modifying a commercial apparatus originally designed to study high temperature electrochemical cells in various gas environments. A grey-box, nonlinear system identification model is utilized to analyze both electrochemical and calorimetric data of BaZr0.8 Ce0.1 Y0.1 O3 based electrochemical cells and achieve a calorimeter electrochemical cell power sensitivity of 16.1 ± 11.7 mW. This operando calorimeter provides the capability to study thermal behaviour of electrochemical cells at elevated temperatures.